Bimatoprost Induced Serous Macular Detachment after Cataract Surgery - Swapnil Parchand; Subashini Kaliaperumal; Amit Kumar Deb; K. Ramesh Babu; Renuka Srinivasan (Case Reports in Ophthalmological Medicine)
We report a case of bimatoprost induced serous macular detachment and choroidal folds following uneventful cataract surgery. A 66-year-old male using topical bimatoprost in both eyes for open angle glaucoma underwent uneventful cataract surgery in the right eye. Postoperatively, he was restarted on topical bimatoprost and antibiotic-steroids combination drops. One week after surgery, he presented with conjunctival hyperemia, serous macular detachment, and choroidal folds at the posterior pole. Fundus fluorescein angiography showed perifoveal leaks in early stage with pooling of dye in late stage. Discontinuation of bimatoprost led to resolution of serous detachment and choroidal folds within 3 weeks with significant improvement in visual acuity. Occurrence of serous macular detachment and choroidal folds in this case could be probably related to the proinflammatory property of bimatoprost. Hence, it should be used with caution in the immediate postoperative period after cataract surgery.